2014
DOI: 10.1002/ange.201402636
|View full text |Cite
|
Sign up to set email alerts
|

Significant Structural Differences between Transient Amyloid‐β Oligomers and Less‐Toxic Fibrils in Regions Known To Harbor Familial Alzheimer′s Mutations

Abstract: Small oligomers of the amyloid b (Ab) peptide, rather than the monomers or the fibrils, are suspected to initiate Alzheimer's disease (AD). However, their low concentration and transient nature under physiological conditions have made structural investigations difficult. A method for addressing such problems has been developed by combining rapid fluorescence techniques with slower two-dimensional solidstate NMR methods. The smallest Ab 40 oligomers that demonstrate a potential sign of toxicity, namely, an enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…ssNMR studies were performed on aggregates of 7S ⌬G25 peptide containing isotopically enriched Val 18 , Phe 19 , Ala 21 , Gly 33 , and Leu 34 residues. These studies revealed that S ⌬G25 fibrils are also rich in ␤-sheet conformations, similar to the amyloid fibrils formed by S and full-length A␤ (20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ssNMR studies were performed on aggregates of 7S ⌬G25 peptide containing isotopically enriched Val 18 , Phe 19 , Ala 21 , Gly 33 , and Leu 34 residues. These studies revealed that S ⌬G25 fibrils are also rich in ␤-sheet conformations, similar to the amyloid fibrils formed by S and full-length A␤ (20).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, small oligomers still form, perhaps driven by the nonspecific intermolecular interactions of the hydrophobic residues. However, the oligomers have random coil architecture and cannot easily grow in size, whereas the oligomers of S and full-length A␤ have at least some ␤-sheet character, and they easily grow to form mature fibrils (7,11,18). The final fibrillar architecture of S ⌬G25 , obtained only at very high concentrations, shows that ␤-sheets do form, but the hairpin opens up, and the ␤-sheet is anti-parallel in nature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A link between monomer misfolding and aggregation propensity and toxicity has been proposed based on experiments (13)(14)(15)(16) and simulations (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) of the naturally occurring alloforms. Those alloforms contain substitutions that occur mainly within the turn region (residues [22][23][24][25][26][27][28][29][30]. Because of the disordered structure of the N-terminus in the fibril structure, the role of this region in aggregation, toxicity, and pathogenesis was considered for a long time to be negligible (27) and therefore remained largely unexplored.…”
Section: Introductionmentioning
confidence: 99%